SER project: analysis of the skills profile of students from three Portuguese professional schools - Neves, Maria de Lurdes; Rodrigues, Rosa (Frontiers in Education, 2024)
This investigation aims to evaluate the effectiveness of the SER project, which focuses on autonomy and curricular flexibility. Additionally, it seeks to assess the profiles of students from three Portuguese vocational schools concerning their social and emotional competencies, self-concept, and personal development following the implementation of the project. The sample comprised 381 students aged between 15 and 20 years. The study employed a quantitative methodology with data collected using the Social and Emotional Skills Questionnaire, the Self-Concept Scale, and the Positive Youth Development Scale. The results revealed that School 1 includes students who tend to exhibit high levels of Social Awareness and Cooperation. School 2, while not excelling in any particular competencies, shows above-average values across all assessed dimensions. Finally, students at School 3 demonstrate elevated levels in Interpersonal Relationships, Self-Esteem, Self-Management, Self-Concept, and Decision-Making. Based on these findings, the study explored whether student profiles differ depending on the school they attend, and it was found that statistically significant differences occur between School 1 and School 2 in Decision-Making and between School 1 and School 3 in Interpersonal Relationships.